İBN HİŞÂM'IN ARAP DİLCİLERİNE YÖNELTTİĞİ TENKİTLER - KUŞÇUOĞLU, ABDULLAH (Fırat Üniveristesi, 2015)
İnsanoğlunun başlangıcından günümüze kadar her geçen gün değişen ve gelişen, hayatı anlamlı kılan, kültürlerin yayılmasına sebep olan en önemli iletişim aracı dildir. Bu bağlamda Arapça, Arap Yarım Adası'ndan doğan, tüm dünyaya yayılan İslâm Dininin dili, geçmişten geleceğe özgün, geniş, zengin kaynakları ile araştırmacıların ilgi odağı, konuşan kişi ve çevrelerin çoğaldığı bir dünya dilidir. Biz bu çalışmamızda Arapça dilbilimcilerinin önde gelenlerinden biri olan İbn Hişâm'ın dönemine kadar Arapça'nın geçirdiği aşamaları, İbn Hişâm'ın yaşadığı dönemin siyâsî, sosyal, iktisâdî, kültürel ve dinî yapısını, dil ekollerine bakış açısını, nahiv konularını işleyiş üslûbunu, kaynaklarının neler olduğunu, öncelik sıralarını ve bazı konularda diğer dilbilimcilere ve ekollerine yöneltmiş olduğu eleştirileri sunmaya ve tahlîl etmeye çalıştık. Anahtar Kelimeler:İbn Hişâm, Kur'ân, Hadîs, Arap Şiirleri, İcmâ, Kıyâs, Dil Ekolleri-Reddiyeler-Delîller.

Language is the most important tool from the beginning of mankind until the present day. It makes life meaningful and it provides to spread of cultures. It develops and changing with each passing day. Arabic is an Islamic language which has born in the Arabian Peninsula and it spans entire world. It has rich language resources, own rules and structure of the original language. It protects its importance at the present day as in the past, its learners and speaking extant grow with each passing day therefore it becomes the status of international language by these features. At this study we prioritize the benefiting resources of this language and we try to analyze its stages and the language schools and Ibn Hisham's style and approach to these schools. At the same time economical, political, social and cultural view for Ibn Hisham's period and his peculiar deduction, and his objections to other nahw scientists, cause and result of these objections constitute the other matters in our analysis. Keywords: Ibn Hisham, the Quran, hadith, Arab poems, Ijma, Qiyas, language schools, objections, evidences
Ibn Hisham's critiques about Arabic linguists
Keywords: Dilbilim; Din; Doğu Dilleri ve Edebiyatı